Baicalein Inhibits the Staphylococcus aureus Biofilm and the LuxS/AI-2 System in vitro [Corrigendum] - Mao Y; Liu P; Chen H; Wang Y; Li C; Wang Q (Infection and Drug Resistance, 2023)
Mao Y, Liu P, Chen H, Wang Y, Li C, Wang Q. Infect Drug Resist. 2023;16:2861–2882. The authors have advised there is an error in the author list on page 2861. The author name “Quiqin Wang” should read “Guiqin Wang”. The authors apologize for this error.